Reference ranges of atrioventricular valve areas by means of four‐dimensional ultrasonography using spatiotemporal image correlation in the rendering mode. (12th November 2012) - Rolo, Liliam Cristine; Nardozza, Luciano Marcondes Machado; Araujo, Edward; Hatanaka, Alan Roberto; Rocha, Luciane Alves; Simioni, Christiane; Moron, Antonio Fernandes
ABSTRACT Objective This study aims to determine reference curves for fetal atrioventricular valve areas by means of three‐dimensional ultrasound using the spatiotemporal image correlation (STIC) software. Methods This was a cross‐sectional prospective study on 328 normal fetuses between the 18th and the 33rd weeks of pregnancy. In order to obtain valve areas, the four heart chambers plane was used with the fetus in a dorsal posterior position. To construct reference ranges, a linear regression model was used, adjusted according to the coefficient of determination (R2). To calculate the reproducibility of the tricuspid valve area, the intraclass coefficient correlation (ICC) was used. Results The mean areas of the tricuspid and mitral valves ranged from 0.19 ± 0.08 and 0.20 ± 0.10 cm2 in the 18th week to 0.93 ± 0.31 and 1.06 ± 0.39 cm2 in the 33rd week, respectively. The intra‐observer and interobserver reproducibility was excellent with ICC = 0.997 and 0.933, respectively. Conclusions Reference curves for fetal atrioventricular valve areas were determined and presented good reproducibility. © 2012 John Wiley & Sons, Ltd.